2021
DOI: 10.1080/2090598x.2021.1959261
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone treatment improves liver function and reduces cardiovascular risk: A long-term prospective study

Abstract: Objectives : To report the association between testosterone treatment in hypogonadal men with hepatic steatosis, non-alcoholic fatty liver disease and cardiovascular disease (CVD). Methods: A prospective study was conducted to assess the physiological and functional performance of the long-term effects of testosterone undecanoate treatment on hepatic steatosis in 496 hypogonadal men. Two groups were studied, the treatment group (T-group) of 312 patients treated with TU 1000 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 75 publications
0
4
1
Order By: Relevance
“…Here liver parameters among KS receiving TRT were within normative ranges. Studies in hypogonadal men have also demonstrated an improvement in liver function after two years of oral testosterone or when increasing the level of testosterone [24,25]. However, the present data did show a trend towards improvement in liver function in T-KS males indicating that TRT may improve liver function in males with KS.…”
Section: Discussioncontrasting
confidence: 84%
“…Here liver parameters among KS receiving TRT were within normative ranges. Studies in hypogonadal men have also demonstrated an improvement in liver function after two years of oral testosterone or when increasing the level of testosterone [24,25]. However, the present data did show a trend towards improvement in liver function in T-KS males indicating that TRT may improve liver function in males with KS.…”
Section: Discussioncontrasting
confidence: 84%
“…In this study, we investigated the potential beneficial effect of testosterone on hepatic histopathological, immunological, and biochemical changes in a CCl 4 -induced mice model. Several studies have shown a relationship between testosterone and liver injury ( Al-Qudimat et al, 2021 ). Even though testosterone treatment improves liver injury and metabolic syndrome, and its effect on type two diabetes mellitus is well-documented ( Sun et al, 2021 ), testosterone effects on hepatic injury are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced liver illness shares many characteristics with hypogonadal males, such as sarcopenia, osteoporosis, gynecomastia, and reduced libido ( Yurci et al, 2011 ). Al-Qudimat A et al suggest that long-term testosterone therapy in hypogonadal men improves liver function ( Al-Qudimat et al, 2021 ). However, it is not fully proven how much testosterone deprivation contributes to the symptoms of severe liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…(•) (6). In 2 prospective studies, for 1 year (n =117) and for 8 years (n = 312), Testosterone treatment improved liver function in non-thalassemic hypogonadal males with hepatic steatosis (•) (77,78).…”
Section: Chronic Hepatitis -Liver Cirrhosismentioning
confidence: 99%